Pengalaman Komunikasi Antar Pribadi Anak dengan Orang Tua Melalui Media Whatsapp pada Kualitas Hubungan Keluarga Mahasiswa UNISSULA Jepara - Tamara Aufa; Fikry Shofin Mubarok (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The background of this research is based on the phenomenon of the increasing use of digital media in maintaining long-distance family communication, in which WhatsApp has become one of the main platforms used. The purpose of this study is to understand the interpersonal communication experiences between children and parents through WhatsApp and its implications for the quality of family relationships among UNISSULA students from Jepara. The research problem formulated in this study is how interpersonal communication experiences between children and parents through WhatsApp affect the quality of family relationships of UNISSULA students from Jepara. This research employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, observation, and documentation with five informants who are students from Jepara studying at UNISSULA Semarang. This study applied the diffusion of innovation theory, which is relevant in explaining how WhatsApp as a communication medium is adopted within the family environment and its influence on the quality of family relationships.The findings show that WhatsApp plays an  important role as an innovative communication medium that not only facilitates the exchange of information but also strengthens emotional bonds between children and parents. Communication through WhatsApp serves dual functions: functional (such as requesting financial support or permission) and affective (emotional support, prayers, and motivation). Family communication patterns have shifted, with digital communication becoming more frequent compared to when living together at home. However, several obstacles were identified, such as parents’ limited digital literacy, technical barriers, intergenerational communication differences, and delayed responses due to busy schedules. Nevertheless, most informants expressed satisfaction with the use of WhatsApp, as it is still able to maintain emotional closeness and family harmony despite geographical distance. Thus, WhatsApp has proven effective as a long-distance communication medium that helps sustain emotional closeness, openness, and the quality of family relationships among UNISSULA students from Jepara, despite technical challenges and generational differences.